2006
DOI: 10.1001/archpedi.160.9.937
|View full text |Cite
|
Sign up to set email alerts
|

Human Herpesvirus 8 Infection Among Adolescents in the REACH Cohort

Abstract: Human herpesvirus 8 is common among US adolescents practicing high-risk sexual behaviors. Sexual identity, race, and sexual behavior may influence the risk of infection with HHV-8 in women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 46 publications
2
16
0
Order By: Relevance
“…2 Since the virus was more prevalent in sexually active men, its sexual mode of transmission was hypothesized. 3,4 However, it has also been reported that HHV-8 can be transmitted through nonsexual routes. 5 In addition, familial clustering of HHV-8 has been observed in highly endemic regions.…”
Section: Introductionmentioning
confidence: 99%
“…2 Since the virus was more prevalent in sexually active men, its sexual mode of transmission was hypothesized. 3,4 However, it has also been reported that HHV-8 can be transmitted through nonsexual routes. 5 In addition, familial clustering of HHV-8 has been observed in highly endemic regions.…”
Section: Introductionmentioning
confidence: 99%
“…2 KS in HIV-negative MSM is rare despite seroprevalence studies showing that 15-30% have the causative virus, human herpes virus 8 (HHV-8). 3,4 There are a number of cases of HIV-negative men presenting with genital lesions of KS, but only a small portion of these report homosexual activity and none have been reported to have been treated with imiquimod. We describe the case of an HIV-negative homosexual man presenting with KS lesions located on the penis that responded rapidly to treatment with topical imiquimod 5% cream.…”
Section: Introductionmentioning
confidence: 99%
“…The Reaching for Excellence in Adolescent Care and Health (REACH) study evaluated youth ages 13-18 years who were at high risk for HIV or were already infected with HIV. The study demonstrated that 11.2% of enrolled youth were HHV-8 antibody positive with no statistically significant difference between those with and without HIV infection [10]. These studies demonstrate a higher than expected seroprevalence for children in select populations living in the United States.…”
mentioning
confidence: 67%